A new approach to the forensic classification of fraud - K. D. Zaiats; D. D. Zaiats (Bulletin of Kharkiv National University of Internal Affairs)
The article substantiates the need to develop a methodology for investigating fraud based on the forensic classification of these criminal offences. It is advisable to choose the criteria for classification of a particular type or group of crimes from the point of view of the practical significance of the differentiation made. Such a criterion ensures grouping of manifestations of crimes based on common features of the mechanism of commission, which, in turn, affects the formation of typical investigative situations of the initial and subsequent stages of investigation, tactical tasks and their solution by appropriate means. The analysis of works by forensic scientists and criminologists who propose to divide frauds into groups depending on the field of activity in which they are committed is made.